Emissions of Greenhouse Gases, Ammonia, and Hydrogen Sulfide from Pigs Fed Standard Diets and Diets Supplemented with Dried Distillers Grains with Solubles. Issue 4 (1st July 2014) - Trabue, Steven; Kerr, Brian
Abstract : Swine producers are supplementing animal diets with increased levels of dried distillers grains with solubles (DDGS) to offset the cost of a standard corn–soybean meal (CSBM) diet. However, the environmental impact of these diets on emissions of greenhouse gases, ammonia (NH3 ), and hydrogen sulfide (H2 S) is largely unknown. Twenty‐four pigs (103.6 kg initial body weight) were fed a standard CSBM diet or a CSBM diet containing 35% DDGS for 42 d. Pigs were fed and their manure was collected twice daily over the 42‐d trial. Pigs fed diets containing DDGS had reduced manure pH ( P < 0.01), increased surface crust coverage ( P < 0.01), increased manure dry matter content ( P < 0.01), and increased manure C ( P < 0.01), N ( P < 0.01), and S ( P < 0.01) contents. Animals fed DDGS diets also had significantly higher concentrations of total ammoniacal nitrogen ( P < 0.01) and sulfide ( P < 0.01) in their manure compared with animals fed CSBM diets. Manure emissions of NH3 ( P < 0.01) and H2 S ( P < 0.05) were significantly higher in animals fed the CSBM diet. There was no dietary treatment effect for methane or nitrous oxide emissions from manure. This study demonstrates that diets containing DDGS can significantly affect manure composition and potentially lower emissions of NH3 and H2 S.